Tumor specific mutations in TERT promoter and CTNNB1 gene in hepatitis B and hepatitis C related hepatocellular carcinoma - Pezzuto, Francesca (Oncotarget, 2016)
Recurrent somatic mutations in the promoter region of telomerase reverse transcriptase (TERT) gene and in the exon 3 of CTNNB1 gene have been recognized as common events in hepatocellular carcinoma (HCC) with variable frequencies depending on etiology and geographical region. We have analyzed TERT promoter and CTNNB1 gene mutations in 122 cases of hepatitis B (HBV) and hepatitis C (HCV) related HCCs, in 7 cases of cholangiocarcinoma (CC) and hepatocholangiocarcinoma (HCC-CC) as well as in autologous cirrhotic tissues. Overall, 50.4% and 26% of HCC as well as 14.3% and none of CC and HCC-CC were mutated in TERT promoter and in CTNNB1 exon 3, respectively. TERT and CTNNB1 mutations were found more frequently in HCV related (53.6% and 26.4%, respectively) than HBV related (41.7% and 16.7%, respectively) HCCs and coexisted in 57.6% of CTNNB1 mutated tumors. Mutations in TERT and CTNNB1 were not associated with the functional promoter polymorphism rs2853669. No mutations were detected in the 129 non-HCC cirrhotic tissues. In conclusion, mutations in TERT promoter and in CTNNB1 gene represent specific cancer signatures in the pathogenesis of viral related HCC and could be promising early biomarkers as well as targets for tailored therapies.